Электропроводящие тонкие пленки для BaCuTeF прозрачных контактов в полупроводниковой электронике - Hotra, Z. Yu.; Tate, J.; Kykyneshi, R.; Zakutayev, А. А.; Rakobovchuk, L. M. (PE "Politekhperiodika", Book and Journal Publishers, 2008)
The chemical composition, structural properties, and electrophysical parameters of BaCuTeF thin films have been investigated. The dependence of the amount of excess copper on the parameters of the deposition process has been studied. The addition of excess copper leads to an increase in film conductivity due to enhanced hole mobility. BaCuTeF thin films can be used for the fabrication of transparent p++ contacts to semiconductor electronic devices.